Obstruction of Justice in Corruption Cases - Yuherawan, Deni Setya Bagus (Universitas Negeri Semarang, 2020)
The purpose of this article is to analyze the investigation authority of the Corruption Eradication Commission (KPK) on the counteraction case of corruption justice process. The reason for the writing is the existence of different interpretation of the authority of the KPK Investigator to conduct an investigation on the counteraction case of justice process in Article 21 of Law No. 31 of 1999 concerning Eradication of Corruption Law junto Law No. 20 of 2001 concerning Amendment to Law Number 31 of 1999 concerning Eradication of the Corruption (the Law of Corruption Act). The analysis method of the problem formulation applies Grammatical Interpretation, Systematic Interpretation, and Teleological Interpretation. The legislation analyzed, besides the Anti-Corruption Law, is the Decree of the People’s Consultative Assembly of the Republic of Indonesia Number XI / MPR / 1998 concerning State Administrators that are clean and free of corruption, collusion, and nepotism; also Law Number 30 of 2002 concerning the Corruption Eradication Commission junto Law Number 10 of 2015 concerning the Establishment of Government Regulations in lieu of Law Number 1 of 2015 concerning Amendments to Law Number 30 of 2002 concerning the Corruption Eradication Commission. The conclusion of this article is that the KPK Investigator is not authorized to conduct an investigation on the counteraction case of corruption justice process.